Konstelasi Tingkat Pengetahuan Dan Risiko Terkena Penyakit Tidak Menular (PTM) Pada Kalangan Remaja (Studi pada Siswa SMA Muhammadiyah Purbalingga) - Subandiyo Subandiyo; Wahyudi Wahyudi (Prodi Keperawatan Purwokerto, 2024)
Background: Adolescence in the community face high risks of non-communicable diseases. Data show that prevalence of non-communicable disease has increased gradually. Life style and environments have mainly caused non communicable diseases. Objective: The study aimed to describe and analysis knowledge and risks factor of non-communicable disease in adolescence in Purbalingga. Methods: The study was cross sectional correlational design. The samples were 60 subjects Muhammadiyah high school in Purbalingga, recruited by stratified random sampling. Data were analyzed with rank spearman test. Results: The finding shows that knowledge of non-communicable diseases could contribute to decrease risks of non-communicable diseases (r=-0,863; p=0,000). Conclusion: It can be highlighted that the high knowledge of non-communicable diseases in adolescence could lead the awareness of non-communicable disease prevention.